Intermittent reinforcement and the persistence of behavior: Experimental evidence - Robin M. Hogarth; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2010)
Whereas economists have made extensive studies of the impact of levels of incentives on behavior, they have paid little attention to the effects of regularity and frequency of incentives. We contrasted three ways of rewarding participants in a real-effort experiment in which individuals had to decide when to exit the situation: a continuous reinforcement schedule (all periods paid); a fixed intermittent reinforcement schedule (one out of three periods paid); and a random intermittent reinforcement schedule (one out of three periods paid on a random basis). In all treatments, monetary rewards were withdrawn after the same unknown number of periods. Overall, intermittent reinforcement leads to more persistence and higher total effort, while participants in the continuous condition exit as soon as payment stops or decrease effort dramatically. Randomness increases the dispersion of effort, inducing both early exiting and persistence in behavior; overall, it reduces agents' payoffs. Our interpretation is that, in the presence of regime shifts, both the frequency and the randomness of the reinforcement schedules influence adjustments that participants make across time to their reference points in earnings expectations. This could explain why agents persist in activities although they lose money, such as excess trading in stock markets.
Keywords: C92; M54; J28; J31; 330; intermittent reinforcement; ambiguity; randomness; incentives; experiment